The Protective Effect of St. Thomas Cardioplegia Enriched With Zacopride on the Isolated Rat Heart. Issue 1 (16th October 2012) - Wu, Bei; Long, Cun; Hei, Feilong; Wang, Shilei
Abstract The activation of the heart inward rectifier potassium channel (IK1) can reduce the injury of myocardial cells by shortening the action potential duration and reducing intracellular calcium overload. Zacopride is a selective IK1 agonist and suppresses triggered arrhythmias in rat hearts. This investigation studied the effects of St. Thomas (ST) cardioplegia enriched with Zacopride on the isolated rat heart model. Sprague‐Dawley rat hearts were harvested and perfused for 20 minutes with 37°C Krebs‐Henseleit (KH) buffer followed by 15 minute perfusion with 4°C calcium‐free KH buffer in the Control group (Con, n = 8), ST cardioplegia in the ST group (ST, n = 8) and ST cardioplegia with Zacopride in the STZ group (STZ, n = 8). After 45 minutes of arresting, all hearts were reperfused with 37°C KH buffer for 60 minutes. Hearts in the STZ group arrested faster than the Con and ST groups (9.25 ± 2.38 s vs. 72.25 ± 8.1 s, 12.75 ± 2.87 s). The recovery of the left ventricular developed pressure, ± dP/dtmax, heart rate, and coronary flow in the STZ group is significantly better than the other two groups during reperfusion. Compared with the Con and ST groups, the STZ group showed significant decreases in the maximum carciac troponin I level (P < 0.05) and the infarct size (P < 0.05). The superoxide dismutase level in the STZ group increased during the first 20 minutes of reperfusion (P < 0.05). ST cardioplegia enriched with Zacopride has beneficial effects against ischemia‐reperfusion injury in this isolated rat heart model.